Ascomycetes fungi of the cloud forest in Mexico - Medel, Rosario (Instituto de Ecología, A.C., 2013)
An update of the species of Ascomycetes recorded for cloud forest in Mexico is presented. Currently, 107 species of Ascomycetes have been recorded in this type of vegetation, of which 69 are present in Veracruz. The taxa correspond to 18 orders, 29 families, and 52 genera. The Xylariaceae is the most diverse family, and Xylaria and Hypoxylon are the genera with the highest number of species. Some of the ecological characteristics of the species were surveyed; it was found that the trophic group of the saprobes is the most diverse, while decaying wood is the substrate where most of the species were found. Regarding the taxonomic diversity of the hosts, 20 families and 22 genera of vascular plants were recorded in association with this group of fungi. At least one family of the fungi recorded in cloud forest (Hyaloscyphaceae) could be considered as recurrent on ferns of the family Cyatheaceae.